2021
DOI: 10.1016/j.ahjo.2021.100052
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular findings on chest computed tomography associated with COVID-19 adverse clinical outcomes

Abstract: Study objective Chest computed tomography (chest CT) is routinely obtained to assess disease severity in COVID-19. While pulmonary findings are well-described in COVID-19, the implications of cardiovascular findings are less well understood. We evaluated the impact of cardiovascular findings on chest CT on the adverse composite outcome (ACO) of hospitalized COVID-19 patients. Setting/participants 245 COVID-19 patients who underwent chest CT at Rush University Health Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…A recent study demonstrated that cardiovascular findings on computed tomography (CT) imaging performed in COVID-19 may be helpful in identifying high-risk patients who may benefit from more intense monitoring and secondary therapies [ 40 ]. Coronary artery calcification (CAC) has been associated with increased mortality in the mid-term and this finds particular significance for those with high levels of CAC such as patients with CAD [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that cardiovascular findings on computed tomography (CT) imaging performed in COVID-19 may be helpful in identifying high-risk patients who may benefit from more intense monitoring and secondary therapies [ 40 ]. Coronary artery calcification (CAC) has been associated with increased mortality in the mid-term and this finds particular significance for those with high levels of CAC such as patients with CAD [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CAC revealed subclinical CAD in COVID-19 patients [9], improving risk stratification. Furthermore, calcium score of the aortic valve, known marker of aortic stenosis, and of the thoracic aorta, marker of atherosclerosis, resulted prognosticators together with CAC [10,26].…”
Section: Acute Cardiovascular Damage: the Role Of Ctmentioning
confidence: 99%
“…RV dysfunction is a common occurrence in COVID-19 pneumonia associated to severity of lung involvement and pulmonary hypertension [41]. CT findings suggestive of RV dilation/dysfunction are RV strain (RV to LV diameter ratio > 0.9), septal flattening due to increased RV pressure, and contrast agent reflux in the inferior vena cava (IVC) [26] (Fig. 2).…”
Section: Acute Cardiovascular Damage: the Role Of Ctmentioning
confidence: 99%
See 2 more Smart Citations